A Study on the Process of Using Project Based Learning in RELT Classroom at English Department IAIN Padangsdidimpuan - Bulan Ritonga (ELITE Association Indonesia, 2023)
ABSTRACT The main purpose of this research is to observe and investigate how is the process of learning research in English Language Teaching by using project based learning at English Department IAIN Padangsidimpuan. The formulation of problems in this research were; 1) How is the process of using project based learning method in RELT classroom? 2) What are the difficulties of using project based learning method in RELT classroom? This research was designed with descriptive qualitative approach. The informants of the research were 15 students of TBI 6th semester. The data were collected by doing observation and interview. The findings revealed that learning activities had been running well, systematically and actively in a class by using PjBL method. The result of this research showed that project based learning can support and enhance students’ motivation and their creativity in the classroom in order to make students easier to understand the explanation by the lecturer. Keywords : Learning Process, Project Based Learning.RELT